2015
DOI: 10.5978/islsm.15-or-08
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Er: YAG or Nd:YAG Laser Exposure on Fluorosed and Non-Fluorosed Root Surfaces: An <i>In vitro</i> Study

Abstract: Background and aims:Fluorosis affects tooth mineralization. The therapeutic benefit provided by lasers on fluorosed and non fluorosed cementum requires studying and comparing. The aim of this study was to evaluate and compare the root surface changes following Er:YAG or Nd:YAG laser irradiation on periodontally healthy fluorosed versus non-fluorosed teeth by scanning electron microscopy (SEM). Materials and methods: A total of 76 periodontally healthy fluorosed (FH) and non-fluorosed (NFH) teeth specimens were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…It has been reported that Nd:YAG laser irradiation promotes the overheating of dental structures followed by their recrystallization [22]. This process results in an acid-resistant, melted dentin surface [23,24] that can impair resin bond infiltration [22]. This can explain the fractures in the laser-irradiated group, which were predominantly of the adhesive type (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that Nd:YAG laser irradiation promotes the overheating of dental structures followed by their recrystallization [22]. This process results in an acid-resistant, melted dentin surface [23,24] that can impair resin bond infiltration [22]. This can explain the fractures in the laser-irradiated group, which were predominantly of the adhesive type (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by Lise et al [16], who observed that the microtensile bond strength of adhesive materials to Nd:YAG-irradiated dentin was lower than to non-irradiated dentin. It has been reported that Nd:YAG laser irradiation promotes the overheating of dental structures followed by their recrystallization [22]. This process results in an acid-resistant, melted dentin surface [23,24] that can impair resin bond infiltration [22].…”
Section: Discussionmentioning
confidence: 99%
“…Other type of lasers such as the CO 2 , Low Level Laser (LLL) have been used in photo-biomodulation therapy to decrease gingival inflammation and enhance the healing process by reducing the essential mediator in the acute inflammatory response known as prostaglandins [15,16]. Moreover, CO 2 lasers have been reported to cause melting of root surfaces similar to Nd:YAG lasers [17,18]. Although the anti-bacterial and ablative effects of laser wavelengths have been discussed widely in the literature [19][20][21], limited laser wavelengths are able to conduct efficient cementum cleaning [22] and are able to create the lowest amount of surface roughness when low levels of energy have been used [23].…”
Section: Introductionmentioning
confidence: 99%
“…Although the anti-bacterial and ablative effects of laser wavelengths have been discussed widely in the literature [19][20][21], limited laser wavelengths are able to conduct efficient cementum cleaning [22] and are able to create the lowest amount of surface roughness when low levels of energy have been used [23]. It is also important to mention that when Er:YAG lasers are used in SRP, neither cracks, microfractures, nor thermal side effects were observed on root surfaces [18].…”
Section: Introductionmentioning
confidence: 99%